Incidence and influencing factors of postoperative frailty in elderly prostate cancer patients: a cross-sectional study - Sun, Li; Ren, Guoqin; Wang, Qin; Zhang, Xumiao; Hua, Hongxia; Gu, Yanglin (Frontiers in Medicine, 2025)
BackgroundPostoperative frailty in prostate cancer patients represents a significant public health concern, as its persistent nature not only impedes recovery but also elevates the risk of adverse clinical outcomes. This study systematically evaluates the prevalence of postoperative frailty and investigates its determinants to establish an evidence-based foundation for developing targeted nursing interventions.MethodsFrom October 2024 to March 2025, a convenience sampling method was employed to select patients undergoing radical prostatectomy in the urology department of a certain tertiary hospital in Wuxi as the research subjects. General information questionnaires’ the VES-13 frailty scale, Karnofsky Performance Status Scale, Sleep Dysfunction Rating Scale, Social Support Rating Scale and Self-Rating Anxiety Scale were used for investigation. Univariate analysis and binary logistic regression were employed to analyze the influencing factors of frailty in postoperative prostate cancer patients.ResultsAmong 306 prostate cancer postoperative patients, 39.5% experienced frailty. Binary logistic regression showed that age, intraoperative blood loss, functional status, exercise frequency (≥3 times/week), anxiety, and social support level were the main influencing factors of frailty (p < 0.05).ConclusionThe incidence of postoperative frailty in prostate cancer patients is high and influenced by various factors. It is recommended that nursing staff actively assess and identify patients, taking proactive measures taking proactive measures to intervene and improve or reverse frailty status.